PVP solid dispersions containing Poloxamer 407 or TPGS for the improvement of ursolic acid release (Brazilian Journal of Pharmaceutical Sciences, 2023)
Solid dispersions (SDs) of ursolic acid (UA) were developed using polyvinylpyrrolidone K30 (PVP K30) in combination with non-ionic surfactants, such as D-α-tocopherol polyethylene glycol 1000 succinate (TPGS) or poloxamer 407 (P407) with the aim of enhancing solubility and in vitro release of the UA. SDs were investigated using a 24 full factorial design, subsequently the selected formulations were characterized for water solubility, X-ray diffractometry (XRD), differential scanning calorimetry (DSC), particle diameter, scanning electron microscopy, drug content, physical-chemical stability and in vitro release profile. SDs showed higher UA water-solubility than physical mixtures (PMs), which was attributed by transition of the drug from crystalline to amorphous or molecular state in the SDs, as indicated by XRD and DSC analyses. SD1 (with P407) and SD2 (with TPGS) were chosen for further investigation because they had higher drug load. SD1 proved to be more stable than SD2, revealing that P407 contributed to ensure the stability of the UA. Furthermore, SD1 and SD2 increased UA release by diffusion and swelling-controlled transport, following the Weibull model. Thus, solid dispersions obtained with PVP k-30 and P407 proved to be advantageous to enhance aqueous solubility and stability of UA.